Analysis of marketing strategies to maximize product sales at "Won.dis Cokelat" - Latifah, Nurul; Hidayah, Nurul (Journal of Halal Science and Research, 2023)
As time progresses, the structure within a business entity changes. Intense competition and business development are factors contributing to these changes. Consequently, each business entity formulates strategies to enhance sales in the competitive market. In this specific practical work, we analyzed the marketing strategy at Won.dis Chocolate to understand how their marketing approach contributes to increased product sales. Data collection techniques employed in this study included qualitative methods such as observation, participation, interviews, literature review, and questionnaires. The data analysis methods included the IFE (Internal Factor Evaluation) matrix, EFE matrix (External Factor Evaluation), SWOT Cartesian diagram analysis, and SWOT matrix. The analysis and observations yielded three key findings. Firstly, Won.dis Chocolate boasts two significant strengths: innovation in new product development and possessing product legitimacy, including halal certification from MUI and intellectual property rights registration. However, its most significant weakness lies in its less strategic location and limited production machine capacity. Secondly, the major opportunity for Won.dis Chocolate lies in its strong relationships with content creators and several universities, while a potential threat is posed by competitors with more strategic locations. Thirdly, Won.dis Chocolate is positioned to pursue both "Grow" and "Build" strategies. Keywords: SWOT analysis, IFE and EFE matrices, Won.dis Chocolate